2010
DOI: 10.1002/hep.23977
|View full text |Cite
|
Sign up to set email alerts
|

Hypercytolytic activity of hepatic natural killer cells correlates with liver injury in chronic hepatitis B patients

Abstract: Natural killer (NK) cells are abundant in the liver and serve as a major innate immune component against microbial infection. Although NK cells have been implicated in inducing hepatocellular damage in patients with chronic hepatitis virus infections, the roles that hepatic NK cells play in chronic hepatitis B virus (HBV) infections remain obscure. In this study, we comprehensively characterized intrahepatic and peripheral NK cells and investigated their impact on liver pathology in a cohort of HBV-infected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
165
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(179 citation statements)
references
References 36 publications
12
165
1
Order By: Relevance
“…NK cell effector functions are finely tuned and timely regulated by many activating receptors and inhibitory receptors (4). Excessive NK cell activation can cause severe immunopathology of the infected tissues or autoimmune diseases (8,47). At an early stage during viral infection, NK cell-produced cytokines play a pivotal role in antiviral immunity and augment further priming of virus-specific CD8 ϩ T cell responses (8,48).…”
Section: Discussionmentioning
confidence: 99%
“…NK cell effector functions are finely tuned and timely regulated by many activating receptors and inhibitory receptors (4). Excessive NK cell activation can cause severe immunopathology of the infected tissues or autoimmune diseases (8,47). At an early stage during viral infection, NK cell-produced cytokines play a pivotal role in antiviral immunity and augment further priming of virus-specific CD8 ϩ T cell responses (8,48).…”
Section: Discussionmentioning
confidence: 99%
“…Their functionality seems often suppressed by the presence of different immunomodulatory cytokines, such as IL-10 or TGF-b (Peppa et al 2010), whereas other data have suggested an increased cytotoxic ability and involvement in liver damage (Zhang et al 2011b). One other interesting possibility is that NK cells, during chronic HBV infection, act as a rheostat of HBV-specific T cells.…”
Section: Nk and Nkt Cells In Hbv Infectionmentioning
confidence: 99%
“…(2) altered expression of activating or inhibitory receptors on NK cells 33,43-46 ; (3) up-regulation of some molecules with inhibitory effects such as T cell immunoglobulin and mucin domain containing molecule-3 (Tim-3); 47 (4) maintained or even enhanced cytolytic activity, which is correlated to the severity of liver injury 33,43,46 ; and (5) impaired capacity to produce cytokines such as IFN-␥ and TNF-␣. 43,44,46,47 Viral load reduction through anti-viral therapy partly restores NK cells numbers, cytokine production and inhibitory receptor expression.…”
Section: Nk Cells In Chronic Hbv Infectionmentioning
confidence: 99%
“…In chronic infection, NK cells display varying changes in proportion, phenotype and/or function, which differ between studies. The defects in NK cells are reflected in many aspects: (1) the percentages of hepatic and peripheral NK cells are reduced in immune-activated CHB patients, with or without changes in their subsets 33,43,44 ;…”
Section: Nk Cells In Chronic Hbv Infectionmentioning
confidence: 99%